White slave crusades: race, gender, and anti-vice activism, 1887 - 1917 - Donovan, Brian (Univ. of Illinois Press, 2006)
White slavery and the intersection of race and gender -- The new abolitionism : the cultural power of the white slavery -- Genre -- Suffrage and slavery : the racial politics of the WCTU's purity -- Campaign -- "The black traffic in white girls" : Chicago's war on vice -- John D. Rockefeller jr. and the "notorious mulatto procuress" -- "Yellow slavery" and Donaldina Cameron's San Francisco mission -- Conclusion.